Essais d'affinage en mer ouverte d'huîtres creuses Crassostrea gigas issues de l'étang de Thau - Oheix, Jocelyne; Coatanea, Denis (1993)
Mud blisters related to the Parasite worm Polydora or to the presence of TBT in the Thau Basin waters depreciate the market value of the oysters produced in this lagoon. A solution to this problem was searched by immersing during 1 to 3 months the oysters in the open sea before being marketed, this shell improvment operation being called "affinage en mer". The objective or this study carried out over 2,5 months in automn '1991 was to quantify possible differences, biometrical or biochemical, between oyster immersed for "affinage" on bottom open-sea structures, or remained for a normal cultivation .in the Thau lagoon. No significant differences were measured, although the external aspect of shells was modified for open sea oysters. Complementary studies at other seasons of the year should be necessary to assess the possible interest of this operation. L'existence de chambrages liés au ver Polydora ou à la présence de TBT dans l'étang de Thau constitue pour la production ostréicole de ce bassin un argument commercial défavorable. Une solution à ce problème a été recherchée en soumettant, avant leur commercialisation, des huîtres élevéës dans l'étang de Thau à une immersion de 1 à 3 mois en mer ouverte, dénommée "affinage en mer". Au cours de cette étude réalisee sur 2,5 mois à l'automne 1991, il n'a pas été possible de quantifier de différences significatives au niveau de la biométrie et de la biochimie entre un lot d'huîtres affinées en pleine mer et un lot équivalent normalement élevé en étang. L'aspect extérieur des coquilles est cependant modifié en pleine mer, et il serait souhaitable de reprendre cette étude à d'autres périodes de l'année plus propices à révéler les possibles avantages de l'affnage en mer